Evaluation of safe bearing capacity of soil foundation by using numerical analysis method - Abdoullah Namdar; Xiong Feng (Fracture and Structural Integrity)
The soil mechanic laboratory results help in accurate soil foundation design and enhancement failure mitigation. The mixing soil design has been used in many geotechnical engineering for soil improvement. In this paper, several types of soil foundations have been made from mixed soil. The bearing capacity of soil foundations by using mixed soil parameters and change footing dimensions have been calculated. 180 footings, placed on 15 soil foundation types have been designed. It is assumed the underground water has not effect to bearing capacity of soil foundation. The results of numerical analysis and mixed soils technique have been combined. The numerical analysis has supported mixed soil design, and introduced an appropriate result for soil foundation design. The effects of mixed soil on depth and width of footing have been compared. The mixed soil design influenced numerical analysis result, and economically, soil foundation design helps to select the appropriate dimensions of footings. The result of numerical analysis supports geotechnical and structural engineering codes, predicts structural stability with different age, natural hazard and prevention as well as it is useful in understanding safe bearing capacity of soil foundation behavior.